Characteristics and related factors of viral nucleic acid negative conversion in children infected with Omicron variant strain of SARS-CoV-2 - Yin, R (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To understand the characteristics and associated factors of viral nucleic acid conversion in children infected with Omicron variant strain of SARS-CoV-2 in Shanghai. Methods: The clinical symptoms, laboratory results and other data of 177 children infected with SARS-CoV-2 who were hospitalized in Shanghai Children's Hospital, School of Medicine, Shanghai Jiao Tong University (designated hospital for SARS-CoV-2 infection in Shanghai) from April 25 to June 8, 2022 were retrospectively analyzed. According to the chest imaging findings, the children were divided into mild and common type groups. According to their age, the unvaccinated children were divided into<3 years old group and 3-<18 years old group. According to the vaccination status, the children aged 3-<18 year were divided into non-vaccination group, 1-dose vaccination group and 2-dose vaccination group. Comparison between groups was performed by independent sample t-test and analysis of variance, and multivariate linear regression analysis was used for multivariate analysis. Results: Among the 177 children infected with Omicron variant of SARS-CoV-2, 96 were males and 81 were females, aged 3 (1, 6) years. The time of viral nucleic acid negative conversion was (10.3±3.1) days. The 177 children were 138 cases of mild type and 39 cases of common type. Among the children aged 3-<18 years old, 55 cases were not vaccinated, 5 cases received 1-dose and 36 cases received 2-dose vaccination. Among the 36 children who received 2 doses of vaccination, the time of viral nucleic acid negative conversion was shorter in those vaccinated within 6 months than those over 6 months ((7.1±1.9) vs. (10.8±3.0) d, t=-3.23, P=0.004). Univariate analysis showed that the time of nucleic acid negative conversion of SARS-CoV-2 was associated with age, underlying diseases, gastrointestinal symptoms, white blood cell count, proportion of neutrophils, proportion of lymphocytes, and the number of doses of SARS-CoV-2 vaccine (t=3.87, 2.55, 2.04, 4.24, 3.51, 2.92, F=16.27, all P<0.05). Multiple linear regression analysis showed that older age (β=-0.33, 95% CI -0.485--0.182, P<0.001) and more doses of vaccination (β=-0.79, 95% CI -1.463--0.120, P=0.021) were associated with shortened nucleic acid negative conversion time in children, while lower lymphocyte proportion (β=-0.02, 95% CI -0.044--0.002, P=0.031) and underlying diseases (β=1.52, 95% CI 0.363-2.672, P=0.010) were associated with prolonged nucleic acid negative conversion time in children. Conclusion: The children infected with Omicron variant of SARS-CoV-2 with reduced lymphocyte proportion and underlying diseases may have longer time of viral nucleic acid negative conversion,while children with older age and more doses of vaccination may have shorter time of viral nucleic acid negative conversion